Expression of cathepsins B and D by cancer stem cells in head and neck metastatic malignant melanoma. Issue 5 (10th June 2021) - Sangster, Adam B.; Chang-McDonald, Bridget; Patel, Josie; Bockett, Nicholas; Paterson, Erin; Davis, Paul F; Tan, Swee T.
Abstract : Supplemental Digital Content is available in the text. Abstract : We have previously demonstrated cancer stem cell (CSC) subpopulations in head and neck metastatic malignant melanoma (HNmMM), and the expression of components of the renin–angiotensin system (RAS) by these CSCs. Cathepsins B, D and G are involved in carcinogenesis and constitute bypass loops of the RAS. This study investigated the expression and localization of cathepsins B, D and G, in relation to these CSCs. Immunohistochemical staining demonstrated expression of cathepsins B, D and G in HNmMM sections from all 20 patients. Western blotting confirmed the presence of cathepsins B and D proteins in all six HNmMM tissue samples and four HNmMM-derived primary cell lines. RT-qPCR showed transcript expression of cathepsins B, D and G in all six HNmMM tissue samples, and cathepsins B and D but not cathepsin G in all four HNmMM-derived primary cell lines. Enzymatic activity assays demonstrated cathepsins B and D were active in all six HNmMM tissue samples. Immunofluorescence staining performed on two of the HNmMM tissue samples demonstrated expression of cathepsins B and D by the CSCs, and cathepsin G by cells within the peritumoral stroma. Our novel findings suggest the possibility of targeting these CSCs by modulation of paracrine RAS signaling.